BASALIT trial: double-blind placebo-controlled allergen immunotherapy with rBet v 1-FV in birch-related soya allergy. - Treudler, R.; Franke, A.; Schmiedeknecht, A.; Ballmer-Weber, B.; Worm, M.; Werfel, T.; Jappe, U.; Biedermann, T.; Schmitt, J.; Brehler, R.; Kleinheinz, A.; Kleine-Tebbe, J.; et al. (Allergy, 2017)
BACKGROUND: Conflicting results exist on the effect of allergen immunotherapy (AIT) on pollen-related food allergy. We aimed to investigate the efficacy of one-year AIT with the folding variant (FV) of recombinant (r) Bet v 1 on birch-related soya allergy. METHODS: Of 138 subjects with Bet v 1 sensitization, 82 were positive at double-blind placebo-controlled food challenge (DBPCFC) with soya. A total of 56 of 82 were randomized in the ratio of 2:1 (active: placebo). Per-protocol population (PPP) had received >/=150 mug of allergen or placebo preparation. OUTCOME MEASURES: lowest observed adverse effect levels (LOAEL), postinterventional occurrence of objective signs (objS) at any dose level, sIgE/IgG4 against Bet v 1 and Gly m 4. Between-group changes were investigated (ancova, Mann-Whitney U-test, Fisher exact test). RESULTS: Baseline characteristics including LOAELs were comparable in both groups with objS and subjS occurring in 82% and 95% of active (n = 38) vs 78% and 83% of placebo group (n = 18). After AIT, objS occurred in 24% and 47%, respectively. LOAEL group differences showed a beneficial tendency (P = 0.081) for LOAEL(objective) in PPP (30 active, 15 placebo). sIgG4 raised only in active group (Bet v 1: P = 0.054, Gly m 4: P = 0.037), and no relevant changes occurred for sIgE. Only 56% of the intended sample size was recruited. CONCLUSION: For the first time, we present data on the effect of rBet v 1-FV on birch-related soya allergy. rBet v 1-FV AIT induced significant immunogenic effects. Clinical assessment showed a tendency in favour of the active group but did not reach statistical significance.
Keywords: Adult; Antigens, Plant/*immunology; Betula/*immunology; *Desensitization, Immunologic/adverse effects/methods; Female; Food Hypersensitivity/*immunology/*therapy; Humans; Immunoglobulin E/blood/immunology; Male; Middle Aged; Quality of Life; Rhinitis, Allergic, Seasonal/diagnosis/*immunology/*therapy; Skin Tests; Glycine max/*adverse effects; Treatment Outcome